2011
DOI: 10.3389/fpsyt.2011.00027
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant NF-KappaB Expression in Autism Spectrum Condition: A Mechanism for Neuroinflammation

Abstract: Autism spectrum condition (ASC) is recognized as having an inflammatory component. Post-mortem brain samples from patients with ASC display neuroglial activation and inflammatory markers in cerebrospinal fluid, although little is known about the underlying molecular mechanisms. Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) is a protein found in almost all cell types and mediates regulation of immune response by inducing the expression of inflammatory cytokines and chemokines, establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 52 publications
5
82
0
Order By: Relevance
“…This suggests that there could be a role for inflammatory pathways in the pathobiology of autism. This is supported by the observation that patients with autism have increased plasma-circulating levels of proinflammatory cytokines [31][32][33][34]. Because acetylcholine suppresses proinflammatory cytokine production and the cholinergic system is altered in autism, it is likely that maternal infections (clinical or subclinical) induced elevation in IL-6 and TNF-a evoke fetal brain injury that could lead to changes in gene expression patterns into the neonatal period.…”
Section: Cholinergic Neurotransmitter System Inflammation and Autismmentioning
confidence: 87%
“…This suggests that there could be a role for inflammatory pathways in the pathobiology of autism. This is supported by the observation that patients with autism have increased plasma-circulating levels of proinflammatory cytokines [31][32][33][34]. Because acetylcholine suppresses proinflammatory cytokine production and the cholinergic system is altered in autism, it is likely that maternal infections (clinical or subclinical) induced elevation in IL-6 and TNF-a evoke fetal brain injury that could lead to changes in gene expression patterns into the neonatal period.…”
Section: Cholinergic Neurotransmitter System Inflammation and Autismmentioning
confidence: 87%
“…36 In accordance with our results, NF-κB upregulation had previously been found in the postmortem PFC of patients with schizophrenia and in patients with other psychiatric diseases, such as depression or autism. [37][38][39] Recently, meta-analysis of gene coexpression networks in the postmortem PFC of patients with schizophrenia and controls found quantitative and clustering alterations in the module including immunity-related genes, such as TLR2, CD14, MYD88 and NFKBIA. 40 Previous studies demonstrated a peripheral imbalance in the TLR4 signalling pathway in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that methylation block at ATXN7 overlaps with transcription factor binding sites (Table S2) where RELA (NF-kappa-B) binds. NF-kappa-B protein mediates the regulation of immune response and its abnormal expression is associated with Autism spectrum condition (ASC) (Young et al 2011), characterized as having an inflammatory component.…”
Section: Discussionmentioning
confidence: 99%